Chemolithoautotrophy supports macroinvertebrate food webs and affects diversity and stability in groundwater communities. Issue 6 (1st June 2016) - Hutchins, Benjamin T.; Engel, Annette Summers; Nowlin, Weston H.; Schwartz, Benjamin F.
Abstract: The prevailing paradigm in subterranean ecology is that below‐ground food webs are simple, limited to one or two trophic levels, and composed of generalist species because of spatio‐temporally patchy food resources and pervasive energy limitation. This paradigm is based on relatively few studies of easily accessible, air‐filled caves. However, in some subterranean ecosystems, chemolithoautotrophy can subsidize or replace surface‐based allochthonous inputs of photosynthetically derived organic matter (OM) as a basal food resource and promote niche specialization and evolution of higher trophic levels. Consequently, the current subterranean trophic paradigm fails to account for variation in resources, trophic specialization, and food chain length in some subterranean ecosystems. We reevaluated the subterranean food web paradigm by examining spatial variation in the isotopic composition of basal food resources and consumers, food web structure, stygobiont species diversity, and chromophoric organic matter (CDOM), across a geochemical gradient in a large and complex groundwater system, the Edwards Aquifer in Central Texas (USA). Mean δ 13 C values of stygobiont communities become increasingly more negative along the gradient of photosynthetic OM sources near the aquifer recharge zone to chemolithoautotrophic OM sources closer to the freshwater‐saline water interface (FWSWI) between oxygenated freshwater and anoxic, sulfide‐rich saline water. Stygobiont community species richness declined with increasing distance from the FWSWI. Bayesian mixing models were used to estimate the relative importance of photosynthetic OM and chemolithoautotrophic OM for stygobiont communities at three biogeochemically distinct sites. The contribution of chemolithoautotrophic OM to consumers at these sites ranged between 25% and 69% of total OM utilized and comprised as much as 88% of the diet for one species. In addition, the food web adjacent to the FWSWI had greater trophic diversity when compared to the other two sites. Our results suggest that diverse OM sources and in situ, chemolithoautotrophic OM production can support complex groundwater food webs and increase species richness. Chemolithoautotrophy has been fundamental for the long‐term maintenance of species diversity, trophic complexity, and community stability in this subterranean ecosystem, especially during periods of decreased photosynthetic production and groundwater recharge that have occurred over geologic time scales.